Preparation method of nano zinc oxide coating on surface of medical porous zinc alloy
Through laser additive manufacturing and crude vacuum sintering technology, porous zinc alloys with nano zinc oxide coatings were prepared, which solved the problem of easy fall off of bioactive coatings, and achieved the optimization design and preparation of personalized pore structures, improving porous Bioactivity and mechanical properties of zinc alloys.
Patent Information
- Application Number
- CN202411597066.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-18
AI Technical Summary
Prior Art When preparing medical porous zinc alloys, the bioactive coating is prone to fall off and it is difficult to achieve personalized optimized design and preparation of pore structures.
Laser additive manufacturing and crude vacuum sintering process are used to prepare porous zinc alloys with macroporous structures, and nano zinc oxide coatings are independently grown on their surface to form a macro-microscopic double-scale composite pore structure.
While ensuring the mechanical properties and modulus of porous zinc alloys, it improves its biological activity, avoids the problem of coating peeling, and realizes the optimized design and preparation of personalized pore structures.
Smart Images

Figure CN119457123A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of laser additive manufacturing and vacuum sintering, and specifically relates to a method for preparing a nano zinc oxide coating on the surface of a medical porous zinc alloy. Background Art
[0002] Existing surveys have found that the non-union rate of large bone defects exceeds 80%, the average annual bone injury function loss rate in China can reach 19.8%, and the amputation rate is as high as 10.4%, resulting in an increase in medical expenses year by year. Clinically, hard tissue replacement is usually used to repair and treat large bone defects. The key lies in the design and manufacture of hard tissue implants. At present, the porous structure design of medical degradable metal materials such as magnesium, iron, zinc and their alloys to obtain an elastic modulus that matches human bone tissue effectively avoids the problem of osteoporosis caused by stress shielding, which has become a research hotspot in the field of orthopedics.
[0003] Zinc, an essential trace element for the human body, is a component of important life substances such as carbohydrates, lipids, proteins and nucleic acids, especially a key element of human bone formation ability. It can participate in human growth and development and effectively maintain the health of the body. At the same time, as a biomedical material, the corrosion rate of zinc is between Mg and Fe, which can adjust the inappropriate degradation rate problem existing in magnesium alloys and iron alloys. Based on the moderate corrosion behavior and excellent mechanical properties of zinc alloys, it has become one of the most promising materials for tissue engineering scaffolds.
[0004] The invention patent with application number 201810836059.2 discloses a method for preparing a porous zinc-silver alloy bioscaffold. The method melts the zinc-silver alloy and pours it into a cylindrical stainless steel mold that has been pretreated with sodium chloride and has a hole at the bottom. The lid is quickly covered and compressed gas is introduced to obtain a porous zinc alloy containing sodium chloride. The sodium chloride is removed by ultrasonic cleaning to obtain a porous zinc with a macroscopic pore structure. This method achieves control of the pore structure by selecting and pretreating sodium chloride particles to obtain a modulus that matches bone tissue, but does not further improve the bioactivity of the zinc alloy from a structural perspective. It is necessary to design a bioactive coating to promote the application of porous zinc alloys. The invention patent with application number 202310315327.7 discloses a porous zinc alloy scaffold, a preparation method and an application. The laser selective melting technology is used to print and prepare porous zinc alloys with body-centered cubic structure, diamond structure and trabecular biomimetic curved surface structure, and the effect of the structure on Zn 2+ The above methods all achieve the macroscopic pore design of porous zinc as a medical implant material, but do not further improve the bioactivity of zinc alloys from a structural perspective. It is necessary to additionally design bioactive coatings to promote the application of porous zinc alloys.
[0005] The invention patent with application number 201910068632.4 discloses a method for preparing nano-scale porous zinc. The method first uses alloy smelting to prepare zinc-magnesium alloy, and then removes the magnesium element in the magnesium alloy by electrochemical corrosion, thereby forming a nano-scale microscopic porous zinc skeleton with interconnectedness. The nano-scale interconnected pore structure constructed by this method can effectively improve the biological activity of zinc alloy, but it cannot achieve effective regulation of the modulus and mechanical properties of porous zinc. The invention patent with application number 202110979802.1 discloses a porous zinc alloy bone tissue engineering scaffold coated with a bioactive coating and a preparation method thereof. The porous zinc alloy is first prepared and cut and acid-treated, and then immersed in a polymer solution such as sodium alginate, pectin, chitosan, etc., and centrifugally dried to obtain a porous zinc alloy bone tissue engineering scaffold with high porosity, adjustable pore size, high strength, and good biological activity. Based on the invention patent 201810836059.2, this method promotes the application of porous zinc alloy in the field of bone tissue repair by preparing an activation coating of zinc alloy. However, this method has a complicated process flow, and the bonding between the prepared coating and the substrate is poor. It is easy to fall off during application and cannot meet the use requirements. To solve the above problems, the invention patent with application number 202311565502.4 discloses a method for preparing a porous zinc alloy with a composite structure based on metal smelting and vacuum infiltration casting technology. This method adds a microporous pore-forming agent TiH2 during the smelting process to simultaneously form a macro-micro composite pore structure porous zinc alloy during the infiltration process. The process of this method is simple, and it can effectively solve the problem of easy shedding of the bioactive coating on the surface of the porous zinc alloy, but the macroscopic pore structure prepared by the infiltration casting process depends on the shape and size of the pore-forming agent, and cannot achieve personalized pore structure optimization design and preparation.
[0006] The invention patent with application number 202311230038.3 discloses a method for preparing a UV-cured magnesium-containing nanoparticle / polycarbonate organic-inorganic hybrid coating on a zinc alloy surface; the invention patent with application number 202211451714.5 discloses a degradable drug-loaded coating on the surface of a zinc alloy implant, and its preparation method and application. These invention patents enrich and develop the preparation methods of bioactive treatment on the surface of medical porous zinc alloys, but all have the problem of poor bonding between the interface and the coating and easy falling off. Summary of the invention
[0007] The technical problem to be solved by the present invention is to provide a method for preparing a nano zinc oxide coating on the surface of a medical porous zinc alloy in view of the deficiencies of the above-mentioned prior art. The method is based on laser additive manufacturing and rough vacuum sintering process, prepares a porous zinc alloy with a macroscopic pore structure and autonomously grows a nano zinc oxide coating on its surface, obtains a macro-micro dual-scale composite pore structure, improves the biological activity of the porous zinc alloy while ensuring the mechanical properties and adaptation modulus of the porous zinc alloy, and realizes the optimized design and preparation of the personalized pore structure, effectively avoiding the problem of easy shedding of the bioactive coating on the surface of the bone implant.
[0008] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a nano zinc oxide coating on the surface of a medical porous zinc alloy, characterized in that a computer pore structure optimization design model is first used, and a laser selective melting process is used to prepare a porous zinc alloy with a macroscopic pore structure according to the modeling results, and then a nano zinc oxide coating is prepared by rough vacuum sintering to obtain a porous zinc alloy with a nano zinc oxide coating.
[0009] The above-mentioned method for preparing a nano zinc oxide coating on the surface of a medical porous zinc alloy is characterized in that the modeling is based on the design criteria of the bone implant to optimize the macroscopic pore structure design. In the implant research, matching the mechanical properties of human bone tissue, having a structure similar to human bone tissue, and having good biocompatibility are used as the design criteria of the bone implant.
[0010] The above-mentioned method for preparing a nano zinc oxide coating on the surface of a medical porous zinc alloy is characterized in that the raw material powder used in the laser selective melting process is spherical powder for 3D printing, with a particle size of 15μm to 53μm, and the raw material powder is mechanically mixed under a vacuum state.
[0011] The above-mentioned method for preparing a nano zinc oxide coating on the surface of a medical porous zinc alloy is characterized in that the parameters of the laser selective melting process are: laser power 60W~120W, scanning speed 200mm / s~800mm / s, and the scanning strategy is strip mode.
[0012] The above-mentioned method for preparing a nano zinc oxide coating on the surface of a medical porous zinc alloy is characterized in that the temperature of the rough vacuum sintering is 450° C. to 650° C., and the sintering time is 0.5 h to 1.5 h.
[0013] The above-mentioned method for preparing a nano zinc oxide coating on the surface of a medical porous zinc alloy is characterized in that, during the rough vacuum sintering process, the vacuum pump is kept working throughout the entire process, and the furnace mouth valve is adjusted to allow air to flow in steadily, maintaining a vacuum degree of 200Pa to 500Pa.
[0014] At the same time, the present invention also discloses a method for preparing a nano zinc oxide coating on the surface of a medical porous zinc alloy, characterized in that the method comprises the following steps:
[0015] Step 1: Select 3D printed spherical zinc powder and titanium powder or iron powder in a mass ratio of 30-70:70-30 and mechanically mix them on a double-shaft horizontal mixer. At the same time, a short zinc rod with a diameter of 10 mm and a length of 20 mm is used as a stirring rod. The speed of mechanical mixing is 200 rpm, the mixing time is 3 h, the rod-to-material ratio is 10:1, and the vacuum degree is less than 50 Pa to obtain a mixed powder;
[0016] Step 2: Based on the design criteria of bone implants, computer modeling software is used to optimize the macroscopic pore structure, and a porous zinc alloy model of TPMS, body-centered cubic or negative Poisson's ratio structure is established. According to the characteristics of bone ingrowth and nutrient transport, the macroscopic porosity of the porous zinc alloy model is designed to be 60% to 90%;
[0017] Step 3: Using the mixed powder obtained in step 1 as a raw material, according to the modeling result in step 2, a porous zinc alloy with a macroscopic pore structure is prepared by a laser selective melting process; the parameters of the laser selective melting process are: single layer powder thickness 30 μm, laser power 60W-120W, scanning speed 200mm / s-800mm / s, and the scanning strategy is strip mode;
[0018] Step 4: Use a vacuum furnace to perform rough vacuum sintering on the porous zinc alloy with a macroporous structure prepared in step 3 to prepare a nano zinc oxide coating, take it out after cooling in the furnace, ultrasonically clean it with anhydrous ethanol for 30 minutes, and then dry it to obtain a porous zinc alloy with a nano zinc oxide coating; the rough vacuum sintering temperature is 450°C to 650°C, the vacuum degree is 200Pa to 500Pa, and the sintering time is 0.5h to 1.5h.
[0019] The present invention uses zinc powder and titanium powder or iron powder as raw material powders, obtains physically doped mixed powder after mechanical mixing, then constructs macroscopic pore structure through computer modeling software, and adopts laser selective melting process to prepare personalized porous zinc alloy with macroscopic pore structure, and then prepares nano zinc oxide coating on the surface of porous zinc alloy with macroscopic pore structure through rough vacuum sintering to obtain porous zinc alloy with nano zinc oxide coating. The porous zinc alloy has a macro-micro dual-scale composite pore structure, which effectively improves the biological activity of porous zinc alloy while meeting the mechanical properties and modulus regulation of porous zinc alloy; at the same time, the macroscopic pore structure and nano zinc oxide structure can be adjusted according to the application requirements of clinical implantation in orthopedics, and the porous zinc alloy obtains a modulus matching bone tissue, better pore connectivity and realizes the regulation of degradation rate through the adjustment of macroscopic pores, and the nano zinc oxide coating formed on the pore ridges effectively improves the biological activity of porous zinc alloy and promotes the adhesion, proliferation and differentiation of osteoblasts.
[0020] The above method is characterized in that the parameters of the laser selective melting process in step three are: laser power 80W, scanning speed 400mm / s, or laser power 120W, scanning speed 600mm / s.
[0021] The above method is characterized in that the temperature of the low-rough vacuum sintering in step 4 is 550° C., the vacuum degree is 300 Pa, and the sintering time is 1 hour.
[0022] The above method is characterized in that the porous zinc alloy in step 4 has both micro-macro pore structure characteristics. The macro pores in this structural feature can not only effectively adjust the modulus and mechanical properties of the porous zinc alloy, but also the micro pores improve the biological activity of the porous zinc alloy, which can well promote the adhesion, growth and differentiation of bone cells.
[0023] Preferably, the microstructure and mechanical properties of the composite structure bioporous zinc alloy can be regulated by subsequent heat treatment.
[0024] Compared with the prior art, the present invention has the following advantages:
[0025] 1. Different from the prior art in which other coatings are introduced after the porous zinc alloy is prepared to improve the biological activity of the porous zinc alloy, the present invention is based on laser additive manufacturing and rough vacuum sintering technology to prepare a porous zinc alloy with a macroscopic pore structure and autonomously grow a nano zinc oxide coating on its surface to obtain a macro-micro dual-scale composite pore structure. While ensuring the mechanical properties and adaptive modulus of the porous zinc alloy, the biological activity of the porous zinc alloy is improved, and it is suitable for the biomedical field.
[0026] 2. Different from the prior art in which the biological coating added on the surface of the porous zinc alloy has poor bonding with the substrate, the present invention autonomously grows a nano zinc oxide coating on the surface of the porous zinc alloy with a macroscopic pore structure through rough vacuum sintering, ensuring that the nano zinc oxide coating and the porous zinc alloy substrate are a whole without the presence of an interface, thus avoiding the problem of poor bonding between the coating and the substrate.
[0027] 3. Different from the powder metallurgy and traditional casting methods that rely on the shape and size of the pore-forming agent to obtain a porous structure, the present invention is based on laser additive manufacturing and rough vacuum sintering technology. By adjusting the laser additive manufacturing process parameters, the macroscopic pore structure is adjusted so that the porous zinc alloy obtains a modulus matching that of bone tissue, better pore connectivity, and achieves regulation of the degradation rate. By adjusting the rough vacuum sintering time, temperature, and vacuum degree, nano zinc oxide structures with different microporous morphologies are formed, which effectively improves the biological activity of the porous zinc alloy and promotes the adhesion, proliferation, and differentiation of osteoblasts, thereby realizing the optimized design and preparation of personalized pore structures and meeting the needs of orthopedic clinical implants.
[0028] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The present invention is a process flow chart for preparing a porous zinc alloy having a nano zinc oxide coating.
[0030] Figure 2 The porous Zn with macroscopic pore structure prepared in Example 1 of the present invention 30 Ti 70 Macroscopic morphology of the alloy.
[0031] Figure 3 The porous Zn with macroscopic pore structure prepared in Example 1 of the present invention 30 Ti 70 Surface micromorphology and EDS element distribution of the alloy.
[0032] Figure 4 The porous ZnO2-coated nanostructured ... 30 Ti 70 Surface micromorphology and EDS element distribution of the alloy. DETAILED DESCRIPTION
[0033] Example 1
[0034] like Figure 1 As shown, this embodiment includes the following steps:
[0035] Step 1: Select 3D printed spherical zinc powder and 3D printed spherical titanium powder with a particle size of 15 μm to 53 μm, and mix them mechanically in a double-shaft horizontal mixer in a mass ratio of 30:70. At the same time, a short zinc rod with a diameter of 10 mm and a length of 20 mm is used as a stirring rod. The speed of mechanical mixing is 200 rpm, the mixing time is 3 h, the rod-to-material ratio is 10:1, and the vacuum degree is less than 50 Pa to obtain a mixed powder;
[0036] Step 2: Based on the design criteria of bone implants, the macroscopic pore structure is optimized by using computer modeling software CAD to establish a G-structure porous zinc alloy model in the TPMS structure. According to the characteristics of bone ingrowth and nutrient transport, the macroscopic porosity of the porous zinc alloy model is designed to be 90%;
[0037] Step 3: Using the mixed powder obtained in step 1 as raw material, according to the modeling results in step 2, a porous ZnO2 with a macroscopic pore structure is prepared by laser selective melting process. 30 Ti 70 alloy, height 5mm, diameter 10mm, such as Figure 2 As shown; the parameters of the laser selective melting process are: single layer powder thickness 30μm, laser power 80W, scanning speed 400mm / s, and scanning strategy is strip mode;
[0038] Step 4: Use a vacuum furnace to treat the porous Zn with a macroscopic pore structure prepared in step 3. 30 Ti 70 The alloy was roughly vacuum sintered to prepare a nano zinc oxide coating, which was taken out after cooling in the furnace, ultrasonically cleaned with anhydrous ethanol for 30 minutes, and then dried to obtain a porous ZnO-coated nanoparticle. 30 Ti 70 alloy; the rough vacuum sintering temperature is 550°C, the vacuum degree is 300Pa, and the sintering time is 1h.
[0039] Figure 3 The porous Zn with macroscopic pore structure prepared in this example 30 Ti 70 The surface microstructure and EDS element distribution of the alloy Figure 3 It can be seen that the distribution of zinc and titanium has a clear interface and the element distribution is concentrated.
[0040] Figure 4 The porous ZnO2-coated nanostructured ZnO2 30 Ti 70 The surface microstructure and EDS element distribution of the alloy Figure 4It can be seen that after rough vacuum sintering, a layer of zinc oxide nanorod coating with a size of about 50 nm is formed on the surface of the alloy. The distribution of Ti, Zn, and O elements can be clearly seen in the EDS elemental analysis, which also proves that the coating product is zinc oxide.
[0041] The 3D printed spherical titanium powder in this embodiment can also be replaced by 3D printed spherical iron powder.
[0042] Example 2
[0043] like Figure 1 As shown, this embodiment includes the following steps:
[0044] Step 1: Select 3D printed spherical zinc powder and 3D printed spherical titanium powder with a particle size of 15 μm to 53 μm, and mix them mechanically in a double-shaft horizontal mixer in a mass ratio of 70:30. At the same time, a short zinc rod with a diameter of 10 mm and a length of 20 mm is used as a stirring rod. The speed of mechanical mixing is 200 rpm, the mixing time is 3 h, the rod-to-material ratio is 10:1, and the vacuum degree is less than 50 Pa to obtain a mixed powder;
[0045] Step 2: Based on the design criteria of bone implants, computer modeling software CAD is used to optimize the macroscopic pore structure, and a body-centered cubic structure porous zinc alloy model is established. According to the characteristics of bone ingrowth and nutrient transport, the macroscopic porosity of the porous zinc alloy model is designed to be 75%;
[0046] Step 3: Using the mixed powder obtained in step 1 as raw material, according to the modeling results in step 2, a porous ZnO2 with a macroscopic pore structure is prepared by laser selective melting process. 70 Ti 30 alloy, with a height of 5 mm and a diameter of 10 mm; the parameters of the laser selective melting process are: single layer powder thickness 30 μm, laser power 60 W, scanning speed 200 mm / s, and the scanning strategy is strip mode;
[0047] Step 4: Use a vacuum furnace to treat the porous Zn with a macroscopic pore structure prepared in step 3. 70 Ti 30 The alloy was roughly vacuum sintered to prepare a nano zinc oxide coating, which was taken out after cooling in the furnace, ultrasonically cleaned with anhydrous ethanol for 30 minutes, and then dried to obtain a porous ZnO-coated nanoparticle. 70 Ti 30 alloy; the rough vacuum sintering temperature is 450°C, the vacuum degree is 200Pa, and the sintering time is 1.5h.
[0048] The 3D printed spherical titanium powder in this embodiment can also be replaced by 3D printed spherical iron powder.
[0049] Example 3
[0050] like Figure 1 As shown, this embodiment includes the following steps:
[0051] Step 1: Select 3D printed spherical zinc powder and 3D printed spherical titanium powder with a particle size of 15 μm to 53 μm, and mix them mechanically in a double-shaft horizontal mixer in a mass ratio of 50:50. At the same time, a short zinc rod with a diameter of 10 mm and a length of 20 mm is used as a stirring rod. The speed of mechanical mixing is 200 rpm, the mixing time is 3 h, the rod-to-material ratio is 10:1, and the vacuum degree is less than 50 Pa to obtain a mixed powder;
[0052] Step 2: Based on the design criteria of bone implants, computer modeling software CAD is used to optimize the macroscopic pore structure, and a porous zinc alloy model with a negative Poisson's ratio structure is established. According to the characteristics of bone ingrowth and nutrient transport, the macroscopic porosity of the porous zinc alloy model is designed to be 90%;
[0053] Step 3: Using the mixed powder obtained in step 1 as raw material, according to the modeling results in step 2, a porous ZnO2 with a macroscopic pore structure is prepared by laser selective melting process. 50 Ti 50 alloy, with a height of 5 mm and a diameter of 10 mm; the parameters of the laser selective melting process are: single layer powder thickness 30 μm, laser power 120 W, scanning speed 800 mm / s, and the scanning strategy is strip mode;
[0054] Step 4: Use a vacuum furnace to treat the porous Zn with a macroscopic pore structure prepared in step 3. 50 Ti 50 The alloy was roughly vacuum sintered to prepare a nano zinc oxide coating, which was taken out after cooling in the furnace, ultrasonically cleaned with anhydrous ethanol for 30 minutes, and then dried to obtain a porous ZnO-coated nanoparticle. 50 Ti 50 alloy; the rough vacuum sintering temperature is 650°C, the vacuum degree is 500Pa, and the sintering time is 0.5h.
[0055] The 3D printed spherical titanium powder in this embodiment can also be replaced by 3D printed spherical iron powder.
[0056] Example 4
[0057] like Figure 1 As shown, this embodiment includes the following steps:
[0058] Step 1: Select 3D printed spherical titanium powder with a particle size of 15 μm to 53 μm and 3D printed spherical titanium powder in a mass ratio of 50:50, and mechanically mix them on a double-axis horizontal mixer. At the same time, a short zinc rod with a diameter of 10 mm and a length of 20 mm is used as a stirring rod. The speed of mechanical mixing is 200 rpm, the mixing time is 3 h, the rod-to-material ratio is 10:1, and the vacuum degree is less than 50 Pa to obtain a mixed powder;
[0059] Step 2: Based on the design criteria of bone implants, computer modeling software CAD is used to optimize the macroscopic pore structure, and a body-centered cubic structure porous zinc alloy model is established. According to the characteristics of bone ingrowth and nutrient transport, the macroscopic porosity of the porous zinc alloy model is designed to be 75%;
[0060] Step 3: Using the mixed powder obtained in step 1 as raw material, according to the modeling results in step 2, a porous ZnO2 with a macroscopic pore structure is prepared by laser selective melting process. 50 Ti 50 alloy, with a height of 5 mm and a diameter of 10 mm; the parameters of the laser selective melting process are: single layer powder thickness 30 μm, laser power 120 W, scanning speed 600 mm / s, and the scanning strategy is strip mode;
[0061] Step 4: Use a vacuum furnace to treat the porous Zn with a macroscopic pore structure prepared in step 3. 50 Ti 50 The alloy was roughly vacuum sintered to prepare a nano zinc oxide coating, which was taken out after cooling in the furnace, ultrasonically cleaned with anhydrous ethanol for 30 minutes, and then dried to obtain a porous ZnO-coated nanoparticle. 50 Ti 50 alloy; the rough vacuum sintering temperature is 450°C, the vacuum degree is 200Pa, and the sintering time is 1.5h.
[0062] The 3D printed spherical titanium powder in this embodiment can also be replaced by 3D printed spherical iron powder.
[0063] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a nano zinc oxide coating on the surface of a medical porous zinc alloy, characterized in that: Firstly, the pore structure optimization design is modeled by computer, and according to the modeling results, a porous zinc alloy with a macroscopic pore structure is prepared by laser selective melting process, and then a nano zinc oxide coating is prepared by rough vacuum sintering to obtain a porous zinc alloy with a nano zinc oxide coating.
2. The method for preparing a nano zinc oxide coating on the surface of a medical porous zinc alloy according to claim 1, characterized in that: The modeling is based on the design criteria of the bone implant to optimize the macro-pore structure design.
3. The method for preparing a nano zinc oxide coating on the surface of a medical porous zinc alloy according to claim 1, characterized in that: The raw material powder used in the laser selective melting process is spherical powder for 3D printing, with a particle size of 15 μm to 53 μm, and the raw material powder is mechanically mixed under a vacuum state.
4. The method for preparing a nano zinc oxide coating on the surface of a medical porous zinc alloy according to claim 1, characterized in that: The parameters of the laser selective melting process are: laser power 60W-120W, scanning speed 200mm / s-800mm / s, and scanning strategy is strip mode.
5. The method for preparing a nano zinc oxide coating on the surface of a medical porous zinc alloy according to claim 1, characterized in that: The temperature of the rough vacuum sintering is 450° C. to 650° C., and the sintering time is 0.5 h to 1.5 h.
6. The method for preparing a nano zinc oxide coating on the surface of a medical porous zinc alloy according to claim 1, characterized in that: During the rough vacuum sintering process, the vacuum pump is kept working throughout the whole process, and the furnace port valve is adjusted to allow air to flow in steadily, maintaining the vacuum degree at 200Pa-500Pa.
7. The method for preparing a nano zinc oxide coating on the surface of a medical porous zinc alloy according to claim 1, characterized in that: The method comprises the following steps: Step 1: Select 3D printed spherical zinc powder and titanium powder or iron powder in a mass ratio of 30-70:70-30 and mechanically mix them on a double-shaft horizontal mixer. At the same time, a short zinc rod with a diameter of 10 mm and a length of 20 mm is used as a stirring rod. The speed of mechanical mixing is 200 rpm, the mixing time is 3 h, the rod-to-material ratio is 10:1, and the vacuum degree is less than 50 Pa to obtain a mixed powder; Step 2: Based on the design criteria of bone implants, computer modeling software is used to optimize the macroscopic pore structure, and a porous zinc alloy model of TPMS, body-centered cubic or negative Poisson's ratio structure is established. According to the characteristics of bone ingrowth and nutrient transport, the macroscopic porosity of the porous zinc alloy model is designed to be 60% to 90%; Step 3: Using the mixed powder obtained in step 1 as a raw material, according to the modeling result in step 2, a porous zinc alloy with a macroscopic pore structure is prepared by a laser selective melting process; the parameters of the laser selective melting process are: single layer powder thickness 30 μm, laser power 60W-120W, scanning speed 200mm / s-800mm / s, and the scanning strategy is strip mode; Step 4: Use a vacuum furnace to perform rough vacuum sintering on the porous zinc alloy with a macroporous structure prepared in step 3 to prepare a nano zinc oxide coating, take it out after cooling in the furnace, ultrasonically clean it with anhydrous ethanol for 30 minutes, and then dry it to obtain a porous zinc alloy with a nano zinc oxide coating; the rough vacuum sintering temperature is 450°C to 650°C, the vacuum degree is 200Pa to 500Pa, and the sintering time is 0.5h to 1.5h.
8. The method for preparing a nano zinc oxide coating on the surface of a medical porous zinc alloy according to claim 7, characterized in that: The parameters of the laser selective melting process in step 3 are: laser power 80W, scanning speed 400mm / s, or laser power 120W, scanning speed 600mm / s.
9. The method for preparing a nano zinc oxide coating on the surface of a medical porous zinc alloy according to claim 7, characterized in that: The temperature of the low-rough vacuum sintering in step 4 is 550° C., the vacuum degree is 300 Pa, and the sintering time is 1 hour.
10. The method for preparing a nano zinc oxide coating on the surface of a medical porous zinc alloy according to claim 7, characterized in that: The porous zinc alloy described in step 4 has both micro-macro pore structure characteristics.
Citation Information
Patent Citations
Preparation method of porous zinc-silver alloy biological scaffold material
CN108977682A
Porous zinc and preparation and application thereof
CN109811396A
Porous zinc alloy bone tissue engineering scaffold coated with bioactive coating and preparation method thereof
CN113633831A
A degradable drug-carrying coating for zinc alloy implant surface and its preparation method and application
CN115779142B
Porous zinc alloy stent, preparation method and application thereof
CN116212104A
Cited By
3D printing method of zinc alloy for bone defect filling
CN119952077A